The Hidden Toll of Airborne Lead: Infant Mortality Impacts of Industrial Lead Pollution - Karen Clay; Edson Severnini; Xiao Wang (Institute of Labor Economics (IZA), 2025)
This paper uses U.S. TRI data on industrial air lead emissions to provide IV estimates of the e?ects of air lead concentration on infant mortality. The causal e?ect of lead on infant mortality is identified by variation in air fugitive lead emissions interacted with wind speed near reporting plants, which together determine local ambient lead concentration. Unlike stack emissions, which occur routinely and may prompt avoidance behavior, fugitive emissions are intermittent and influenced by both historical and current factors, such as wind speed variation, making them di?cult to avoid. The paper has two main findings. First, higher air lead concentration causes higher infant mortality in the first month and in the first year, suggesting that both in utero and environmental exposures matter. Second, higher lead concentration increases deaths from low birthweight, sudden unexplained infant death, and respiratory and nervous system causes, which is consistent with findings from animal studies, even when accounting for behavioral responses. Back of the envelope calculations indicate that declines in industrial air lead emissions prevented 300+ infant deaths per year, generating benefits of 3.5+ billion annually in 2023 dollars.
Keywords: I12; Q53; Q58; 330; infant mortality; airborne lead pollution; Toxic Release Inventory (TRI)